ANALISIS SISTEM PENGENDALIAN INTERNAL PADA PENGELUARAN DANA KAS KECIL (STUDI KASUS PT. SUMBER BAHAGIA KARGO EKSPRESS) - Natalia, Yolanda; Novika; Tigor , Ryan Hasianda (STIE IBEK Pangkalpinang, 2023)
This study aims to analyze the internal control system on petty cash disbursements at PT. Sumber Bahagia Kargo Ekspress which has been decided through standard operational management policies. Researchers also use the approach in this research study of literature. Based on the analysis in this study, the internal control system for petty cash disbursements has not been running effectively (theoretical comparisons and research findings in the field) at PT. Sumber Bahagia Kargo Ekspress. The results of the study show that there is no serial number printed on each proof of petty cash disbursement and petty cash disbursement documents that have been made that are not stamped with the mark